Impact of informal social support on the mental health of older adults - Dong, Yi; Cheng, Lanyan; Cao, Hailin (Frontiers in Public Health, 2024)
Objective The role of informal social support in fostering active aging within the context of the “silver wave” is significant. This study investigated how such support influenced the mental health of older adults, with the goal of affirming its indispensable contribution to enhancing their psychological well-being. Methods Employing Principal Component Analysis (PCA) to construct the informal social support variable, this study rigorously analyzed the effects and underlying mechanisms of informal social support on mental health in older adults, utilizing data from the 2018 China Longitudinal Aging Social Survey (CLASS). Results Informal social support exerted a substantial positive influence on the mental health of older adults, particularly among younger, non-agricultural older adult populations who preferred cohabitation with their children. This form of support significantly enhanced mental well-being by elevating life satisfaction, improving access to medical services, and fostering active social engagement. Conclusion This study elucidates the role of informal social support in bolstering the mental health of older adults. Future efforts should focus on fostering a supportive environment that enhances older adult care experiences, reforming the healthcare system to better meet the needs of the aging population, and promoting avenues for social engagement, thereby achieving a balanced integration of their emotional and physical care.